Innovation in flexible housing for modern affordable housing solution in Malaysia - Mohd Noor, Mohd Zairul (CRC Press, 2019)
There has been an increasing interest in flexible housing in the market due to the changes in social household’s structure and lifestyles. Considering this need, this chapter reports on a new model of flexZhouse, based on a thesis entitled flexZhouse: A New Business Model for Affordable Housing in Malaysia, developed as an alternative to current housing solutions that is known as static, immobile and bulky. The idea of flexZhouse emphasises the issue of sustainability in the construction and innovations in the housing market in terms of pricing and design. This chapter aims to explore the innovations in flexible housing based on findings from a design workshop and focus groups conducted for the study. Although the concept is still premature, flexZhouse provides a first idea of how design flexibility and innovation can be achieved for modern affordable housing in Malaysia. This chapter contributes to the body of knowledge in flexible and open building studies and benefits the affordable housing industry, particularly in Malaysia.